2016
DOI: 10.11622/smedj.2015103
|View full text |Cite
|
Sign up to set email alerts
|

Unusual morphology of scapulae: incidence and dimensions of ossified ligaments and supraspinous bony tunnels for clinical consideration

Abstract: INTRODUCTIONKnowledge of anatomical variations and anomalies along the course of the suprascapular nerve (SSN) is important in the treatment of SSN entrapment syndrome, and bony and brachial plexus injuries. This knowledge is also important for surgeons carrying out surgical interventions at the shoulder region.The SSN provides sensory innervation to the posterosuperior aspect of the shoulder and motor innervation to the supraspinatus and infraspinatus muscles. The SSN passes beneath the superior transverse sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 43 publications
2
8
0
Order By: Relevance
“…In general, the correlation analyses of our study have shown that the scapular dimensions (scapular length and width; glenoid length and width) might be of value in the diagnosis, assessment, and prevention of SN entrapment syndrome associated with scapulae of type III, IV and VI SSN emphasizing the clinical significance of scapular dimensions in helping clinicians, radiologists, and orthopedic surgeons perform better with minimal complications in agreement with previous findings [ 1 3 ].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In general, the correlation analyses of our study have shown that the scapular dimensions (scapular length and width; glenoid length and width) might be of value in the diagnosis, assessment, and prevention of SN entrapment syndrome associated with scapulae of type III, IV and VI SSN emphasizing the clinical significance of scapular dimensions in helping clinicians, radiologists, and orthopedic surgeons perform better with minimal complications in agreement with previous findings [ 1 3 ].…”
Section: Discussionsupporting
confidence: 91%
“…The knowledge of the anatomy and variations of SSN is important for clinicians and surgeons that carry out diagnoses, assessment, management, surgical interventions at the shoulder region. This knowledge is vital in the diagnosis, management, assessment, and prevention of suprascapular nerve entrapment disorder around the shoulder joint [ 1 3 ]. The suprascapular notch (SSN) forms a depression on the lateral aspect of the superior border of the scapula, medial to the coracoid process [ 4 ], is bridged by the superior transverse scapular ligament (STSL), which may sometimes be completely ossified with a resultant conversion of the notch into a foramen [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…In general, the correlation analyses of our study have shown that the scapular dimensions (scapular length and width; glenoid length and width) might be of value in the diagnosis, assessment, and prevention of SN entrapment syndrome associated with scapulae of type III, IV and VI SSN emphasizing the clinical signi cance of scapula, glenoid and other related scapular dimensions in helping clinicians, radiologists, and orthopaedic surgeons. perform better with minimal complications [1][2][3]. However, the equation that can be used to predict the relationship of different scapular dimensions and the SSN types could not be determined.…”
Section: Discussionmentioning
confidence: 99%
“…of suprascapular notch variations are important in the management and prevention of the SSN entrapment syndrome, and bony and brachial plexus injuries, furthermore, this knowledge is important for clinicians and surgeons that carry out diagnoses, assessment, management and surgical interventions at the shoulder region and in the prevention of this disorder. [1][2][3]. The suprascapular notch (SSN) forms a depression on the lateral aspect of the superior border of the scapula and located medial to the coracoid process [4], is bridged by the superior transverse scapular ligament (STSL), which may sometime be ossi ed with a resultant conversion of the notch into a foramen [4].…”
Section: Introductionmentioning
confidence: 99%
“…The knowledge of the anatomy and variations of SSN is important for clinicians and surgeons that carry out diagnoses, assessment, management, surgical interventions at the shoulder region. This knowledge is vital in the diagnosis, management, assessment, and prevention of suprascapular nerve entrapment disorder around the shoulder joint [1][2][3]. The suprascapular notch (SSN) forms a depression on the lateral aspect of the superior border of the scapula, medial to the coracoid process [4], is bridged by the superior transverse scapular ligament (STSL), which may sometimes be completely ossi ed with a resultant conversion of the notch into a foramen [4].…”
Section: Introductionmentioning
confidence: 99%